Design of a Programmable System for Failure Modes and Effect Analysis of Steam-Power Plant Based on the Fault Tree Analysis - Al-Khafaji, Soroor K. Hussain; Al-Rahman, Nihad M. A.; Ahmad Al- Dauod, Zuhair I. (Al-Khwarizmi Engineering Journal, 2017)
In this paper, the system of the power plant has been investigated as a special type of industrial systems, which has a significant role in improving societies since the electrical energy has entered all kinds of industries, and it is considered as the artery of modern life.   The aim of this research is to construct a programming system, which could be used to identify the most important failure modes that are occur in a steam type of power plants. Also the effects and reasons of each failure mode could be analyzed through the usage of this programming system reaching to the basic events (main reasons) that causing each failure mode. The construction of this system for FMEA is depending on the logical relationships of the fault tree analysis for the systems that contained in the power station.   The designing of such system could be used as an assistance tool for the specialist user (the power engineer) in identifying of all reasons and effects for any type of failures. So this is help to fastening the repairing operation of the identified failure mode to improve the efficiency of operating system as represented by the maintainability, which is a function of system reliability.   The selection of the steam type of power generation systems for the application of this study, because this type is the most common type of Iraqi power plants. While such the designed system could be programmed to be use in another types of industrial systems.